Is SA law and policy equipped to deal with the peculiarities of Human Trafficking? - Houston, Lorna (Department of Public Law, 2020)
Tens of thousands of men, women and children are being trafficked around the world and brutally exploited. This research investigated if SA law and policy is equipped to deal with the peculiarities of Human Trafficking. This dissertation's central thesis is that the legal and policy response to human trafficking in South Africa is inadequate to deal with its peculiarities. The anti-trafficking response must extend beyond the application of human rights and criminal law to include a cross-cutting, multi-sectoral, socio-economic and political response that addresses its causes and consequences. The study considers and explores the definition of human trafficking, its causes, consequences and the peculiarities and specificities of human trafficking in SA. The international, regional and domestic legal frameworks and their relevance for human trafficking is outlined with emphasis on the Prevention and Combatting of Trafficking in Persons Act 7 of 2013 and the National Policy Framework. A feminist lens using Intersectionality and Standpoint Theory, is applied to inform the critical analysis of the research question. This thesis demonstrated that South Africa's law and policy although promising, is insufficient in dealing with the peculiarities of human trafficking. The law needs to better account for the root causes of trafficking. It is essential that this response is informed by intersectionality to enable the implementation of broader solutions especially addressing the violation of social and economic rights and the root causes of trafficking.